A systematic review and meta-analysis of the effect of whole body cryotherapy on mental health problems - Julia J.R. Doets; Maurice Topper; Annet M. Nugter (Elsevier, 2021)
Objective: To give an overview of the nature and methodological quality of studies on whole body cryotherapy (WBC) as add-on intervention for mental health problems. Methods: A meta-analysis according to PRISMA guidelines was conducted (Prospero registration: CRD42020167443). Databases MEDLINE, PsycINFO and the Cochrane Library were searched. Risk of bias was scored according to the Cochrane ROBINS-I-tool to which an extra bias-dimension of allegiance bias was added. Within and between Hedges' g pooled effect sizes were calculated for the main aspect of mental health measured. Treatment efficacy was examined using a random effects model. Heterogeneity was examined through identification of visual outliers and by I2 statistics. Results: Out of 196 articles coming up from the search, ten studies met all inclusion criteria, six of which were (randomized) controlled trials. Together these studies report on a total of 294 participants receiving WBC. The within-group pooled effect size for mental health problems is large (Hedges' g = 1.63, CI: 1.05-2.21), with high heterogeneity (I2 = 93%). Subgroup analyses on depressive symptoms and quality of life (QOL) showed a diminution of heterogeneity to moderate. Effect sizes for depressive symptoms are very large (Hedges' g = 2.95, CI: 2.44-3.45) and for QOL medium (Hedges' g = 0.70, CI: 0.15-1.24). The between-group pooled effect size is medium (Hedges' g = 0.76, CI: 0.17-1.36). Conclusions: Results indicate preliminary evidence for WBC as efficacious add-on intervention for mental health problems, especially depressive symptoms. Further research in the form of RCTs with larger numbers of participants is needed.